2017
DOI: 10.18632/oncotarget.17446
|View full text |Cite
|
Sign up to set email alerts
|

The generation and functional characterization of induced pluripotent stem cells from human intervertebral disc nucleus pulposus cells

Abstract: Disc degenerative disease (DDD) is believed to originate in the nucleus pulposus (NP) region therefore, it is important to obtain a greater number of active NP cells for the study and therapy of DDD. Human induced pluripotent stem cells (iPSCs) are a powerful tool for modeling the development of DDD in humans, and have the potential to be applied in regenerative medicine. NP cells were isolated from DDD patients following our improved method, and then the primary NP cells were reprogramed into iPSCs with Senda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…The authors' literature review suggests that there are no studies indicating a potential treatment modality for IVD (3,9,23,34).…”
Section: █ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors' literature review suggests that there are no studies indicating a potential treatment modality for IVD (3,9,23,34).…”
Section: █ Discussionmentioning
confidence: 99%
“…They observed that IPSCSs, which originate from NP cells, induced the synthesizing of pluripotent markers in normal karyotype, NPcell specific matrix protein and related genes. They maintained that IPSCSs, which were produced from NPC cells that are peculiar to IVD cases, could be treated by a carrier scaffold (such as hydrogel) in IVD cases (34).…”
Section: █ Discussionmentioning
confidence: 99%
“…The primary cell culture method of NP was similar to others [ 55 ]. Briefly, human intervertebral disc NP tissues derived from the patients with LDH or LSS were rinsed and minced into small fragments of about 1 mm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Since then, a wide variety of studies have reported the derivation of specific cell types from iPSCs, generating robust and reproducible phenotypes in vitro that reflect diseases intrinsic to the cellular level [ 35 ]. Specifically, evidence that reprogrammed cells can be differentiated into osteoblasts [ 54 , 55 , 56 ], chondrocytes [ 57 , 58 , 59 , 60 ], myoblasts [ 61 ], nucleus pulposus cells [ 47 , 48 , 49 ] and tenocytes [ 62 ] has recently impacted musculoskeletal research and changed orthopedic medicine. Nevertheless, the use of iPSCs for studying the wide variety of musculoskeletal conditions has been explored to a limited extent ( Table 1 ) in comparison with conditions affecting nervous or cardiac pathologies, even when investigating genetic disorders where symptoms affect several organs or systems [ 63 , 64 , 65 , 66 ].…”
Section: Disease Modelingmentioning
confidence: 99%
“…Efficient and robust differentiation of iPSCs into tissue-specific cell types is crucial both for disease modeling and for regenerative medicine. Should the reader seek a more detailed explanation about iPSC differentiation protocols, please see the previously published studies on osteogenic [ 3 , 30 , 43 , 44 , 45 ], chondrogenic [ 3 , 27 , 30 , 46 ], nucleus pulposus [ 47 , 48 , 49 ] and/or myogenic [ 3 , 30 , 50 ] differentiation of iPSCs.…”
Section: Introductionmentioning
confidence: 99%